Training on Business Planning Using Business Canvas Models - I Nyoman Tri Sutaguna; Akhmad Nur Zaroni; Erlina Pakki; Arief Yanto Rukmana; Puspita Puji Rahayu (Universitas 45 Surabaya, 2023)
The business world is expanding in Indonesia right now, especially among millennials and start-ups in this case. They must, however, have a mature and well-defined corporate plan because of the intense rivalry and challenging obstacles they encounter. Because the Business Model Canvas can summarize a business strategy on a dialog box page with 9 items, it is believed to be simple, comprehensive, and effective for business planning. The purpose of this service project is to offer BMC model-based business advice and training to Taruna Bakti Bandung Senior High School students. Counseling methods included the lecture style and focus group discussions (FGD). As a result of their community service projects, students are able to develop company ideas using the BMC model.